(untitled) (Bangladesh Journal of Medical Education, 2023)
Background: The clinical skill center (CSC) offers an opportunity for students and working clinicians to learn and acquire clinical skills by using artificially simulated process, which will subsequently improve patient care and safety. To promote skill-based dental education, a CSC might be considered to incorporate in undergraduate dental education. Objectives: To explore the views of the stakeholders about the role of clinical skill centers in undergraduate dental education. This study also identified the effect of clinical skill training in promoting and maintaining clinical teaching. Method: A cross sectional study was carried out among 637 dental persons in 11 dental colleges and units of medical colleges of Bangladesh; of which 5 were government and 6 were non-government. Study period was from January 2022 to December 2022. Data was collected by structured self-administered questionnaire, about the views of the stake holders (Dental teachers, interns and students of 3rd and 4th phases of BDS course). Results: With regard to advantages of CSC, 545 (80.4%) respondents agreed that CSC facilitate skill training before performing on real patient. More so, 544 (90.3%) respondents agreed that CSC increases scope of repeated practice, 360 (64.7%) respondents felt that CSC training helped in overcoming the resistance by the patients who were not interested to intervene them by the trainees and 531(88.5%) agreed that skill training in CSC will reduce medical error. Regarding limitations of CSC, 419 (69.6%) respondents opined that establishing and maintaining CSC are very costly. Total 548 (90.9%) respondents agreed that CSC requires formally trained trainer, 550 (91.6%) respondents felt that CSC needs formally trained supporting staffs, and 533 (89%) agreed that CSC requires well defined infrastructure. Conclusion: The study strongly suggests stakeholder’s positive perspective towards learning clinical skills in CSC. Medical educators, policy makers and curriculum designers can use the results of this study to incorporate clinical skill center based learning in undergraduate curriculum and establish CSC to train and enhance students’ clinical skills and maintain patients’ safety. Bangladesh Journal of Medical Education Vol.14(2) July 2023: 60-71